A comparison of rapid methods including imprint cytodiagnosis for the diagnosis of breast tumours. Issue 4 (April 1973) - Tribe, C. R.
Abstract : Rapid diagnoses were made on 510 breast lumps by three methods in sequence and the results compared with those obtained by paraffin histology. Naked-eye examination of the excised lumps correctly distinguished between benign and malignant tumours in 95·1% of cases with 23 (4·5%) false negative and two (0·4%) false positive results. Rapid imprint cytodiagnosis was correct in 96·9% of the 391 lumps imprinted with 12 (3·1%) false negatives and no false positive results. Frozen sections gave the correct diagnosis in 99·4% of the 510 cases with three (0·6%) false negative and no false positive results. The use of cytology in the diagnosis of breast tumours is discussed.